2018
DOI: 10.1186/s12886-018-1004-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between sunlight exposure and risk of age-related macular degeneration: a meta-analysis

Abstract: BackgroundA substantial number of epidemiological studies have investigated the possible associations between sunlight exposure and Age-related Macular Degeneration (AMD), but the results from studies are inconsistent. The aim of this meta-analysis was to evaluate the association between sunlight exposure and the risk of AMD.MethodsRelevant studies were searched using databases including PubMed, EMBASE, and Web of Science database. Two authors independently extracted data and assessed study quality. The random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 37 publications
0
38
2
Order By: Relevance
“…Collectively, our data with others indicate that contrary to widely held theories, L/ML may not be harmful in AMD. One theory suggests that L/ML are phototoxic, yet retinal illuminance is uniform well beyond the 21° diameter macula,76,77 and epidemiologic data do not support lifetime sunlight exposure as an AMD risk factor 78,79. This same theory builds on the deleterious effects of treating cultured cells with bisretinoid fluorophore A2E, yet this L/ML component is reliably lower in macula than in peripheral retina,4348 a distribution not detectable in early studies analyzing whole eyecups 80.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our data with others indicate that contrary to widely held theories, L/ML may not be harmful in AMD. One theory suggests that L/ML are phototoxic, yet retinal illuminance is uniform well beyond the 21° diameter macula,76,77 and epidemiologic data do not support lifetime sunlight exposure as an AMD risk factor 78,79. This same theory builds on the deleterious effects of treating cultured cells with bisretinoid fluorophore A2E, yet this L/ML component is reliably lower in macula than in peripheral retina,4348 a distribution not detectable in early studies analyzing whole eyecups 80.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have demonstrated an association between UVA and AMD, there is still controversy. It was recently reported that sunlight exposure may not be a risk factor for AMD [37]. Therefore, it is necessary to elucidate the mechanisms of UVA irradiation effects on RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is a recognized factor that is associated with mitochondrial dysfunction in the outer retina. Other important risk factors for the development of AMD are genetics and environmental stressors, including smoking and exposure to ultraviolet and blue light [18,19,20,21,22,23,24]. All of these factors are likely to result in mtDNA damage in the RPE.…”
Section: Mitochondrial Dysfunction With Aging and Diseasementioning
confidence: 99%
“…Although in vitro studies have unequivocally demonstrated that either UV or blue light damage RPE cells [22], epidemiological evidence of the association between exposure to sunlight and AMD is mixed [23]. The ability of the ocular media (cornea, lens, and vitreous humor) to block UV and blue light and the protection of the retina by antioxidant systems, including superoxide dismutase and glutathione peroxidase and macular pigments, including melanin and flavoproteins likely explain these differences [17].…”
Section: Mitochondrial Dysfunction With Aging and Diseasementioning
confidence: 99%
See 1 more Smart Citation